Club-militants, institutionalists, critics, moderns and globalists: A quantitative governance-based typology of football supporters. (December 2020) - García, Borja; Llopis-Goig, Ramón
This article presents a quantitative typology of football fans' attitudes towards governance. Data collection is done through an online survey in six European countries: France, Germany, Poland, Spain, Turkey and the United Kingdom. Results reveal the existence of five types of supporters: club-militants, institutionalists, critics, moderns and globalists. The critics, moderns and globalists fans share a preoccupation for football governance problems but differ in the intensity of their views. At the same time, critics and globalists are heavy consumers of football games and merchandise. The results suggest that existing fan typologies that understand supporters in dichotomic terms of authenticity or consumerism fail to explain the complex reality of a game that has developed new structures over recent decades. Existing typologies need to be superseded in favour of a more multi-disciplinary approach that integrates a governance turn to inform a more nuanced and better understanding of football's social reality.